Phenoloxidase -activity in different tropical prawns and its sensitivity to sulphiting agents - Chakrabarti, R (Indian Journal of Fisheries, 2011)
Presence and characteristics ofphenoloxidase in Indian prawn were reportedby Antony et al. (1968, 1975) andSavagaon et al. (1978). They also tried tofind out probable factors responsible formelanosis. They reported high order ofphenoloxidase activity in head juice and tailextract of Indian prawn. Sovagaon et al.(1978) reported the existence of zymogenform of phenoloxidase in penaeid prawn andgave possible mechanism of activation byendogenous proteolytic enzymes. Thepolyphenolase reactions are accelerated bycopper and other metallic ions (Fieger et al.1961). Antony et al. (1968) reported that pHof tissue, exposure to higher temperature upto 55Â°C and access to oxygen are importantfactors for black spot formation.